The problem of the center for cubic differential systems with two affine non-parallel invariant straight lines of total multiplicity three - Alexandru Șubă (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
In this paper, we show that a center-focus critical point of cubic differential systems with two affine non-parallel invariant straight lines of total multiplicity three is a center type if and only if the first five Lyapunov quantities vanish.